Spontaneous closure of branchial sinus of the pyriform fossa. (14th May 2018) - Liu, Zhaobo; Mohd Slim, Mohd Afiq; Jackson, Conor; Trimble, Keith
Abstract : Management of third and fourth branchial cleft anomalies are similar. These anomalies should be suspected in a child with recurrent low-anterior neck abscess. Investigations in the form of cross-sectional studies and examination of the pharynx under anaesthesia will facilitate diagnosis and resolution of abscess. Spontaneous closure of the pyriform sinus can occur following conservative management with antibiotic treatment and abscess drainage. This emphasise the role of second-look prior to implementing endoscopic cauterisation or surgery.